A Cooperative Way to Learn "Comprehensible Writing" - Kroop, Sylvana; Mangler, Jürgen (Proceedings of the International Conference on Networked Learning, 2006)
Writing texts is difficult although a crucial ability for students. Courses that try to communicate these skills to students often focus on technical issues like correct referencing and scientific working. Writing texts that are understandable even for non-experts is a completely different problem. In an interdisciplinary setting this problem is even more present. "Comprehensible Writing" is the title of a current blended-learning project at the University of Vienna that tries to support the learning of this skill via the introduction of a blended-learning course setting including online learning modules. After highlighting the educational and theoretical background of our work, we will present our project, as well as the blended-learning scenarios that allow for cooperative writing of understandable texts. We will then conclude with a report about the evaluation of the scenarios in an expert workshop.